Method for modifying boride ceramic powder with Mo

By modifying Mo on the surface of boride ceramic powder and using chemical reaction and heat treatment technology, the problem of uneven dispersion of Mo in ceramic powder is solved, which significantly improves the fracture toughness and performance of boride ceramics, and achieves efficient performance promote.

CN119161191AActive Publication Date: 2024-12-20SHANDONG UNIV OF TECH

Patent Information

Application Number
CN202411451214.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2024-12-20
Estimated Expiration
2044-10-17

AI Technical Summary

Technical Problem

The prior art is difficult to achieve uniform dispersion of the refractory metal Mo in the boride ceramic, resulting in its agglomeration in the ceramic powder, affecting the improvement of the performance of the material.

Method used

Mo is modified on the surface of the boride ceramic powder particles through chemical reactions, and the Mo compound is mixed with the boride ceramic powder, and uniformly distributed Mo powder particles are obtained by hydrogen reduction, and heat treatment is carried out to ensure uniform dispersion of Mo.

Benefits of technology

The uniform dispersion of Mo in the ceramic powder is achieved, which significantly improves the fracture toughness and performance of boride ceramics, reduces the preparation cost, simplifies the process flow, and avoids the oxidation of borides.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119161191A_ABST
    Figure CN119161191A_ABST
Patent Text Reader

Abstract

The invention relates to a method for modifying boride ceramic powder by Mo, which comprises the following steps of: uniformly mixing boride ceramic powder (HfB2, ZrB2, NbB2, TaB2 and TiB2) and Mo-containing compounds (MoO2, MoO3, Na2MoO4, H2MoO4, (NH4) 6. Mo7O24, (NH4) 2. Mo4O13 and (NH4) 2. Mo2O7) serving as raw materials, and performing heat treatment in a protective atmosphere and a reducing atmosphere, so that Mo particles are coated on the surfaces of the ceramic powder particles, and the ceramic powder is prevented from being oxidized and impurity phases are prevented from being generated. The method can realize modification of Mo on the surface of the boride powder, so that the refractory metal Mo and the ceramic powder are uniformly mixed, and powder agglomeration is avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The technical solution of the invention is used for preparing Mo-modified boride ceramic powder, and belongs to the field of powder preparation. Background Art

[0002] Ultrahigh temperature ceramics (UHTCs) have excellent oxidation resistance and ablation resistance, extremely high melting point, high thermal conductivity and low thermal expansion coefficient, and are therefore considered to be candidate materials for hypersonic vehicle thermal protection components and propulsion system components of recoverable launch vehicles. Ultrahigh temperature boride ceramics mainly refer to a class of ceramic materials represented by transition metal borides such as zirconium boride (ZrB2), hafnium boride (HfB2), tantalum boride (TaB2) and niobium boride (NbB2), which have the characteristics of high melting point, high hardness, low density, good mechanical properties and high temperature stability. However, boride ceramics have problems such as difficulty in sintering and poor fracture toughness, which limits the practical application of this type of ceramic material.

[0003] Many researchers choose to introduce additives into boride ceramics to improve their fracture toughness. Common additives are divided into ceramic phase and metal phase. Ceramic phase additives, such as SiC, Si3N4, AIN, WC and B4C, can effectively improve the mechanical properties, oxidation resistance and ablation resistance of boride ceramics. However, ceramic phase additives are difficult to significantly improve the fracture toughness of boride ceramics. Metal phase additives, such as refractory metals such as Ni, Nb, Hf, Mo and Ta, have high melting points and good ductility, which is theoretically helpful for enhancing the fracture toughness of boride ceramics. However, a large number of literatures show that refractory metal additives do not have a significant toughening effect on boride ceramics. This is mainly because the traditional mixing method cannot effectively disperse the metal phase evenly in the boride ceramic phase, and the metal phase agglomerates, which affects the improvement of the performance of boride ceramics. Among the metal phase additives, Mo has low density, high melting point and a thermal expansion coefficient similar to that of borides. It is a potential additive that can significantly improve the performance of boride ceramics.

[0004] Boride ceramic materials are brittle and have poor fracture toughness, which makes them unable to meet the requirements of materials in harsh environments such as high-temperature thermal protection in the aerospace field. Therefore, it is very important to use a new technical solution to improve the performance of boride ceramics, which is of great significance for the expansion of the application of boride ceramics in the future. The present invention is expected to significantly improve the performance of boride ceramic materials by in-situ modification of boride powder to achieve uniform coating of Mo on its surface. Summary of the invention

[0005] The purpose of the technical solution of the present invention is to provide a new method for introducing refractory metal Mo into boride ceramic powder, so as to solve the problems of uneven dispersion of metal Mo and easy agglomeration of Mo powder particles existing in the existing method for introducing refractory metal Mo, and to achieve uniform dispersion of Mo in ceramic powder, thereby providing a raw material basis for the preparation of high-performance boride-Mo composite materials.

[0006] The present invention is to modify the metal Mo on the surface of boride ceramic powder particles through chemical reaction. Mo compound is mixed with boride ceramic powder and reduced by hydrogen to obtain refractory metal Mo. The Mo powder obtained can be evenly distributed in the boride ceramic powder, and the fine Mo powder particles can coat the boride ceramic powder particles to complete the surface modification of the boride ceramic powder by the refractory metal Mo.

[0007] Compared with the existing means of introducing refractory metal Mo, the advantage of the present invention is that the refractory metal Mo additive is added to the boride ceramic powder by chemical reaction, and the problems of powder particle agglomeration and uneven dispersion of metal phase are solved. At the same time, by accurately controlling the heat treatment process conditions, the reaction between the boride and the oxide is avoided to cause the oxidation of the boride. In addition, the preparation cost of the scheme of the present invention is low, the process is simple and the time cycle is short. The present invention provides new ideas and methods for the surface modification of boride powders and the performance improvement research of ultra-high temperature ceramics.

[0008] The present invention is a method for Mo-modified boride ceramic powder, which is carried out according to the following steps: (1) Mixing a Mo-containing compound and a boride ceramic powder uniformly, wherein the Mo-containing compound is MoO2, MoO3, Na2MoO4, H2MoO4, (NH4)6·Mo7O 24 、(NH4)2·Mo4O 13 , (NH4)2·Mo2O7; the boride ceramic powder is one or more of HfB2, ZrB2, NbB2, TaB2, TiB2; (2) transferring the mixed powder obtained in step (1) into a tube furnace and pretreating the powder in a protective atmosphere; (3) The product obtained in step (2) is placed in a reducing atmosphere and further heat treated at 300-800° C. to finally obtain a Mo-modified boride ceramic powder.

[0009] In step (1), the mass ratio of the boride ceramic powder to the Mo-containing compound is 1:1-100:1, the Mo-containing compound and the boride ceramic powder are mixed evenly, and the grinding time is 10-60 min.

[0010] In step (2), the preheating treatment is carried out in Ar or N2 gas, the gas flow rate is 0.1-1000 mL / min, the heating rate is 0-100 ℃ / min, the heat treatment temperature is 200-600 ℃, and the holding time is 1-300 min.

[0011] In step (3), the heat treatment is carried out in H2 gas or H2 / Ar mixed gas, wherein the volume fraction of H2 in the H2 / Ar mixed gas is 0.1-50%, the gas flow rate is 0.1-1000 mL / min, the heating rate is 0.1-100 ℃ / min, the heat treatment temperature is 300-800 ℃, and the holding time is 1-360 min. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 This is the X-ray diffraction (XRD) diagram of the Mo-modified ZrB2 powder prepared in Example 1. Figure 2 The scanning electron microscopy (SEM) image and energy dispersive spectrometer (EDS) image of the Mo-modified ZrB2 powder prepared in Example 1 are shown in FIG. Figure 3 This is the X-ray diffraction (XRD) diagram of the Mo-modified ZrB2 powder prepared in Comparative Example 1. Figure 4 The scanning electron microscopy (SEM) image and energy dispersive spectrum (EDS) image of the Mo-modified ZrB2 powder prepared in Comparative Example 1 are shown in FIG. Figure 5 The bending fracture curves of the ceramic samples obtained by sintering the Mo-modified ZrB2 powder prepared in Example 1 and Comparative Example 1 are shown in FIG. Figure 6 The bending fracture curves of the ceramic samples obtained by sintering the Mo-modified ZrB2 powders prepared in Examples 2-7 respectively. DETAILED DESCRIPTION

[0013] The present invention will be further described below in conjunction with the embodiments. The scope of the present invention is not limited to the following embodiments. Those skilled in the art will appreciate that various changes and modifications may be made to the present invention without departing from the spirit and scope of the present invention.

[0014] The instruments, reagents, and materials involved in the following examples, unless otherwise specified, are all conventional instruments, reagents, and materials available in the prior art and can be obtained through regular commercial channels. The experimental methods, detection methods, etc. involved in the following examples, unless otherwise specified, are all conventional experimental methods and detection methods available in the prior art. Example

[0015] Embodiment 1, a method for Mo-modified boride ceramic powder, comprising the following steps: (1) ZrB2 and (NH4)2·Mo4O 13 Weigh the materials at a mass ratio of 1:1 and grind and mix in a mortar for 30 minutes; (2) The mixed powder was placed in a tube furnace and heated, with Ar gas as the protective gas and an Ar gas flow rate of 200 mL / min. The heat treatment process was: heating to 500 °C at a heating rate of 10 °C / min and keeping warm for 30 min. (3) The sample was heated from 500 °C to 620 °C at a heating rate of 10 °C / min, and the Ar gas was switched to H2 (5 vol.%) / Ar with a H2 (5 vol.%) / Ar gas flow rate of 300 mL / min; the sample was kept at 620 °C for 240 min, then the temperature was reduced to 600 °C at a rate of 10 °C / min and then cooled in the furnace while the H2 / Ar gas was kept flowing. The sample was taken out after cooling to room temperature; In the Mo-modified ZrB2 powder prepared in this embodiment, the purity of Mo is 98.32%, and Mo is evenly dispersed in the ZrB2 powder. Figure 1 , SEM and EDS see Figure 2 The Mo-modified ZrB2 powder prepared in this example was hot-pressed and sintered at 1800°C, 30 min, and 30 MPa. The maximum load of the obtained ceramic sample was 607.18 N, and the fracture toughness was 4.72 MPa·m 1 / 2 The bending fracture curve of the specimen is shown in Figure 5 .

[0016] Embodiment 2, a method for Mo-modified boride ceramic powder, comprising the following steps: (1) Weigh ZrB2 and MoO3 in a mass ratio of 15:1 and grind and mix them in a mortar for 45 min; (2) The mixed raw materials were placed in a tubular furnace for heating, with Ar gas as the protective gas and an Ar gas flow rate of 300 mL / min. The mixture was heated to 500 °C at a heating rate of 10 °C / min and kept at this temperature for 30 min. (3) Heating to 630 °C at a heating rate of 10 °C / min and keeping at 630 °C for 180 min; when the temperature of the tube furnace is 630 °C, switching the Ar gas to H2 (10 vol.%) / Ar with a H2 (10 vol.%) / Ar gas flow rate of 100 mL / min; then, decreasing the temperature to 500 °C at a rate of 10 °C / min and cooling with the furnace, keeping the gas flowing, and taking it out after cooling to room temperature; The purity of Mo in the Mo-modified ZrB2 powder prepared in this embodiment is 98.73%, and Mo is evenly dispersed in the ZrB2 powder. The Mo-modified ZrB2 powder prepared in this embodiment is hot-pressed and sintered at 1800°C, 30 min, and 30 MPa. The maximum load of the obtained ceramic sample is 574.16 N, and the fracture toughness is 3.89 MPa·m 1 / 2 The bending fracture curve of the specimen is shown in Figure 6 .

[0017] Embodiment 3, a method for Mo-modified boride ceramic powder, comprising the following steps: (1) Weigh HfB2 and H2MoO4 in a mass ratio of 24:1 and mix them by wet mechanical ball milling for 60 min; (2) The mixed powder sample was placed in a tubular furnace for heating, with N2 gas as the protective gas and a N2 gas flow rate of 300 mL / min. The temperature was heated to 600 °C at a heating rate of 8 °C / min and kept at this temperature for 40 min. (3) Heating to 800 °C at a heating rate of 8 °C / min and keeping at 800 °C for 360 min; when the temperature of the tube furnace is 800 °C, convert the N2 gas to H2 with a H2 gas flow rate of 50 mL / min; then, reduce the temperature to 400 °C at a rate of 8 °C / min and cool with the furnace, keeping the gas flowing, and take it out after cooling to room temperature; In the Mo-modified HfB2 powder prepared in this embodiment, the purity of Mo is 97.83%, and Mo is evenly dispersed in the HfB2 powder. The Mo-modified HfB2 powder prepared in this embodiment is hot-pressed and sintered at 1800°C, 30 min, and 30 MPa. The maximum load of the obtained ceramic sample is 568.31 N, and the fracture toughness is 4.05 MPa·m 1 / 2 The bending fracture curve of the specimen is shown in Figure 6 .

[0018] Embodiment 4, a method for Mo-modified boride ceramic powder, comprising the following steps: (1) Weigh HfB2 and MoO2 in a mass ratio of 76:1 and mix them by dry mechanical ball milling for 15 min; (2) The mixed powder sample was placed in a tube furnace for heating, with Ar gas as the protective gas and an Ar gas flow rate of 150 mL / min. The temperature was heated to 250 °C at a heating rate of 5 °C / min and kept at this temperature for 60 min. (3) Heating to 750 °C at a heating rate of 5 °C / min and keeping at 750 °C for 300 min; when the temperature of the tube furnace is 750 °C, switching the Ar gas to H2 (20 vol.%) / Ar with a H2 (20 vol.%) / Ar gas flow rate of 350 mL / min; then, decreasing the temperature to 200 °C at a rate of 5 °C / min and cooling with the furnace, keeping the gas flowing, and taking it out after cooling to room temperature; In the Mo-modified HfB2 powder prepared in this embodiment, the purity of Mo is 98.53%, and Mo is evenly dispersed in the HfB2 powder. The Mo-modified HfB2 powder prepared in this embodiment is hot-pressed and sintered at 1800°C, 30 min, and 30 MPa. The maximum load of the obtained ceramic sample is 498.21 N, and the fracture toughness is 3.76 MPa·m 1 / 2 The bending fracture curve of the specimen is shown in Figure 6 .

[0019] Embodiment 5, a method for Mo-modified boride ceramic powder, comprising the following steps: (1) Weigh NbB2 and Na2MoO4 in a mass ratio of 37:1 and grind and mix them in a mortar for 30 min; (2) The mixed powder sample was placed in a tubular furnace for heating, with N2 gas as the protective gas and a N2 gas flow rate of 200 mL / min. The temperature was heated to 450 °C at a heating rate of 10 °C / min and kept at this temperature for 30 min. (3) Heating to 650 °C at a heating rate of 10 °C / min, and keeping at 650 °C for 360 min; when the temperature of the tube furnace is 650 °C, convert the N2 gas to H2 with a H2 flow rate of 70 mL / min; then, reduce the temperature to 400 °C at a rate of 10 °C / min and cool with the furnace, keeping the gas flowing, and take it out after cooling to room temperature; In the Mo-modified NbB2 powder prepared in this embodiment, the purity of Mo is 96.94%, and Mo is evenly dispersed in the NbB2 powder. The Mo-modified NbB2 powder prepared in this embodiment is hot-pressed and sintered at 1800°C, 30 min, and 30 MPa. The maximum load of the obtained ceramic sample is 501.37 N, and the fracture toughness is 4.69 MPa·m 1 / 2 The bending fracture curve of the specimen is shown in Figure 6 .

[0020] Embodiment 6, a method for Mo-modified boride ceramic powder, comprising the following steps: (1) TaB2 and (NH4)6·Mo7O 24The materials were weighed at a mass ratio of 19:1 and mixed by wet mechanical ball milling for 50 min; (2) The mixed powder sample was placed in a tubular furnace for heating, with N2 gas as the protective gas and a N2 gas flow rate of 100 mL / min. The temperature was heated to 600 °C at a heating rate of 5 °C / min and kept at this temperature for 45 min. (3) Heating to 800 °C at a heating rate of 5 °C / min and keeping at 800 °C for 240 min; when the temperature of the tube furnace is 800 °C, convert the N2 gas to H2 (7 vol.%) / Ar with a H2 (7 vol.%) / Ar gas flow rate of 200 mL / min; then, reducing the temperature to 600 °C at a rate of 5 °C / min and cooling with the furnace, keeping the gas flowing, and taking it out after cooling to room temperature; The purity of Mo in the Mo-modified TaB2 powder prepared in this embodiment is 97.91%, and Mo is evenly dispersed in the TaB2 powder. The Mo-modified TaB2 powder prepared in this embodiment is hot-pressed and sintered at 1800°C, 30 min, and 30 MPa. The maximum load of the obtained ceramic sample is 541.88 N, and the fracture toughness is 4.10 MPa·m 1 / 2 The bending fracture curve of the specimen is shown in Figure 6 .

[0021] Embodiment 7, a method for Mo-modified boride ceramic powder, comprising the following steps: (1) Weigh TaB2 and (NH4)2·Mo2O7 in a mass ratio of 100:1 and grind and mix them in a mortar for 25 minutes; (2) The mixed powder sample was placed in a tubular furnace for heating, with Ar gas as the protective gas and an Ar gas flow rate of 250 mL / min. The mixture was heated to 580 °C at a heating rate of 10 °C / min and kept at this temperature for 60 min. (3) Heating to 750 °C at a heating rate of 10 °C / min and keeping at 750 °C for 240 min; when the temperature of the tube furnace is 750 °C, switching the Ar gas to H2 (15 vol.%) / Ar with a H2 (15 vol.%) / Ar gas flow rate of 100 mL / min; then, decreasing the temperature to 500 °C at a rate of 10 °C / min and cooling with the furnace, keeping the gas flowing, and taking it out after cooling to room temperature; The purity of Mo in the Mo-modified TaB2 powder prepared in this embodiment is 96.98%, and Mo is evenly dispersed in the TaB2 powder. The Mo-modified TaB2 powder prepared in this embodiment is hot-pressed and sintered at 1800°C, 30 min, and 30 MPa. The maximum load of the obtained ceramic sample is 522.61 N, and the fracture toughness is 3.68 MPa·m 1 / 2 The bending fracture curve of the specimen is shown in Figure 6 .

[0022] Comparative Example 1: The difference from Example 1 is that in step (2) and step (3), the temperature is raised to 150°C at 15°C / min in an Ar gas atmosphere, kept at this temperature for 10 min, then raised to 280°C at 15°C / min, the Ar gas is converted to H2 (1 vol.%) / Ar, and kept at this temperature for 50 min; the other experimental conditions are the same. The purity of Mo in the Mo-modified ZrB2 powder prepared in this comparative example is 95.43%. The XRD characteristics of the powder are shown in Table 1. Figure 3 , SEM and EDS see Figure 4 ; Combined with Figure 2 It can be clearly seen that the dispersion uniformity of Mo in the Mo-modified ZrB2 powder obtained in Comparative Example 1 is lower than that in Example 1; the maximum load of the ceramic sample obtained by sintering the Mo-modified ZrB2 powder prepared in this comparative example under the same sintering process as in Example 1 is 455.23 N, and the fracture toughness is 2.39 MPa·m 1 / 2 The bending fracture curve of the specimen is shown in Figure 5 It is the high dispersion uniformity of Mo in ZrB2 powder in Example 1 that ensures the uniformity of the composite ceramic structure obtained after sintering, thereby improving the mechanical properties of the material.

[0023] Comparative Example 2: The difference from Example 1 is that the grinding time is set to 5 min instead of 30 min. The other experimental conditions are the same. In the Mo-modified ZrB2 powder prepared in this comparative example, the purity of Mo is 84.72%, and the dispersion uniformity of Mo in the ZrB2 powder is lower than that in Example 1. Figure 1 It can be seen that the XRD diffraction peaks of the Mo-modified ZrB2 powder obtained in Example 1 are completely consistent with the standard PDF cards of ZrB2 and Mo, and there are no extra impurity peaks. Figure 2 It can be seen that the distribution of Mo in the Mo-modified ZrB2 powder obtained in Example 1 is very uniform and there is no obvious agglomeration phenomenon.

[0024] In public reports, most scholars choose to introduce Mo into boride ceramic powders by ball milling, but this method makes it difficult to evenly distribute Mo and easily leads to Mo agglomeration. In comparison, the method of introducing Mo into ceramic powders by reducing Mo-containing compounds with H2 can achieve uniform distribution of Mo in the ceramic powders, and through appropriate heat treatment process control, oxidation of boride powders can be avoided. Therefore, this method provides a new feasible solution for Mo-modified boride ceramic powders.

Claims

1. A method for modifying boride ceramic powder with Mo, characterized in that: The preparation process includes the following steps: (1) Mixing a Mo-containing compound and a boride ceramic powder uniformly, wherein the Mo-containing compound is MoO2, MoO3, Na2MoO4, H2MoO4, (NH4)6·Mo7O 24 、(NH4)2·Mo4O 13 , (NH4)2·Mo2O7; the boride ceramic powder is one or more of HfB2, ZrB2, NbB2, TaB2, TiB2; (2) transferring the mixed powder obtained in step (1) into a tube furnace and pretreating the powder in a protective atmosphere; (3) The product obtained in step (2) is placed in a reducing atmosphere and further heat treated at 300-800° C. to finally obtain a Mo-modified boride ceramic powder.

2. The method for Mo-modified boride ceramic powder according to claim 1, characterized in that: In step (1), the mass ratio of the boride ceramic powder to the Mo-containing compound is 1:1-100:

1.

3. The method for Mo-modified boride ceramic powder according to claim 1, characterized in that: In step (1), the powders are mixed by dry mechanical ball milling, wet mechanical ball milling or mortar grinding, and the mixing time is 1-600 min.

4. The method for Mo-modified boride ceramic powder according to claim 1, characterized in that: The protective atmosphere in step (2) is Ar or N2, the gas flow rate is 0.1-1000 mL / min, the heating rate is 0-100 ℃ / min, the heat treatment temperature is 200-600 ℃, and the holding time is 1-300 min.

5. The method for Mo-modified boride ceramic powder according to claim 1, characterized in that: The reducing atmosphere in step (3) is H2 gas or H2 / Ar mixed gas, wherein the volume fraction of H2 in the H2 / Ar mixed gas is 0.1-50%, the gas flow rate is 0.1-1000 mL / min, the heating rate is 0.1-100 ℃ / min, the heat treatment temperature is 300-800 ℃, and the holding time is 1-360 min.

Citation Information

Patent Citations

  • Composite powder formed by zirconium diboride-silicon carbide coated with high-melting-point metal

    CN107695345A

  • Boride ceramic with high toughness and high heat conductivity and preparation method and application thereof

    CN110526716A

  • Ultrahigh-temperature high-entropy boride ceramic powder and preparation method thereof

    CN111848177A

  • Core-shell structure composite powder and preparation method thereof

    CN114769583A

  • Ultrahigh-hardness high-entropy metal boride ceramic and low-temperature pressure-free preparation method thereof

    CN115894042A

Cited By

  • Preparation method of Mo toughened boride-based ultra-high-temperature ceramic

    CN120117906A